2005
DOI: 10.1093/aje/kwi241
|View full text |Cite
|
Sign up to set email alerts
|

Is the Risk of Lung Cancer Reduced among Eczema Patients?

Abstract: Persons with a history of eczema have been shown to have a reduced risk of lung cancer, but the evidence has been inconclusive because of the small size of previous studies and their limited ability to control for confounding by smoking. The objective of this study was to determine the role of eczema in relation to lung cancer while overcoming the limitations of previous investigations. Study subjects included 2,854 cases and 3,116 population and hospital controls recruited during 1998-2001 from 16 areas in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 21 publications
3
36
0
3
Order By: Relevance
“…Even the published discussion immediately after the publication of the second study brought up the notion that several confounders such as the use of allergy and asthma medication might pose important confounding factors [23]. Other epidemiological studies have shown differing results for different types of cancer, for example a protective effect (negative association) between atopy and colorectal cancer or leukemia and a positive association between atopy and lung or prostate cancer [21,24,25]. Thus, a new research field was opened and the discussion is still ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Even the published discussion immediately after the publication of the second study brought up the notion that several confounders such as the use of allergy and asthma medication might pose important confounding factors [23]. Other epidemiological studies have shown differing results for different types of cancer, for example a protective effect (negative association) between atopy and colorectal cancer or leukemia and a positive association between atopy and lung or prostate cancer [21,24,25]. Thus, a new research field was opened and the discussion is still ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies [19,20], we identified patients with a baseline comorbidity including asthma (ICD-9-CM code 493), chronic obstructive pulmonary …”
Section: Definition Of Skin Manifestationsmentioning
confidence: 99%
“…There has been an expansion of the epidemiological literature aimed at investigating correlations between a clinical history of allergies and cancer development. Biological markers of a history of allergies have been evaluated, including those pertaining to immune function such as immunoglobulin E (IgE) levels [115]. However, the epidemiological data linking allergy and cancer development have yet to be confirmed in experimental models.…”
Section: Allergooncologymentioning
confidence: 99%
“…To explain positive or direct associations, McWhorter proposed a “theory of antigenic stimulation” in 1988 [115117], a theory that has since been revisited [118, 119]. The theory of antigenic stimulation suggests that allergies lead to chronic inflammation and cell growth stimulation, which increases the probability of mutations in actively dividing cells and the generation of aberrant clones.…”
Section: Allergooncologymentioning
confidence: 99%